Janus v. AFSCME, Council 31: An Unprecedented Blow to Public Sector Unions? - Sophia Carter (Bellarmine Law Society Review, 2021)
In June of 2018, the Supreme Court of the United States handed down a shocking opinion that sent waves through labor law and the public sector. After forty-one years of state and local labor law policy being structured around the precedent set by Abood vs. Detroit Board of Education (c. 1977), the Supreme Court overturned the right of public sector unions to enter into agency-shop agreements, which otherwise necessitates the payment of fees to the union regardless of union membership. In this article, I will first briefly discuss the facts of Janus, both parties’ contentions, and the reasoning behind the opinions of both the conservative majority and the liberal minority. I will then argue that Janus was incorrectly decided under the well-established doctrine of stare decisis and that the practical implications of the majority’s decision run counter to the spirit of public sector labor rights.